Monocyte/macrophage lineage commitment and distribution are affected by the lack of regulatory T cells in scurfy mice. Issue 7 (27th May 2016) - Skuljec, Jelena; Cabanski, Maciej; Surdziel, Ewa; Lachmann, Nico; Brennig, Sebastian; Pul, Refik; Jirmo, Adan C.; Habener, Anika; Visic, Julia; Dalüge, Kathleen; Hennig, Christian; Moritz, Thomas; et al.
Abstract : Treg cell‐deficient scurfy mice have increased generation and recruitment of monocytes/macrophages. Adoptive transfer of WT CD4 + cells and M‐CSF‐neutralization reversed abnormal monocyte distribution. Injection of Treg cells to RAG2 −/− mice had no effect on myelopoiesis suggesting that disturbed monocyte/macrophage homeostasis in scurfy mice is a consequence of ongoing inflammation. Abstract : Foxp3 + regulatory T (Treg) cells play a pivotal role in maintaining immunological tolerance. Loss‐of‐function mutations in the Foxp3 gene result in multiorgan inflammation known as immunodysregulation, polyendocrinopathy, enteropathy, X‐linked syndrome in humans and scurfy (Sf) disease in mice. While the impact of missing Treg cells on adaptive immune cells is well documented, their role in regulation of myeloid cells remains unclear. Here we report that Sf mice exhibit an altered composition of stem and progenitor cells, characterized by increased numbers of myeloid precursors and higher efficiency of macrophage generation ex vivo. The proportion of monocytes/macrophages in the bone marrow, blood, and spleen was significantly elevated in Sf mice, which was accompanied with tissue‐specific monocyte expression of homing receptor and phagocytic activity. Sf mice displayed high levels of M‐CSF and other inflammatory cytokines, including monocyte‐recruiting chemokines. Adoptive transfer of WT CD4 + cells and in vivo neutralization of M‐CSF normalized frequencies of monocyte subsets and their progenitors and reduced high levels of monocyte‐related cytokines in Sf mice, while Treg cell transfer to RAG2 −/− mice had no effect on myelopoiesis and monocyte/macrophage counts. Our findings illustrate that deregulated myelopoiesis in Sf mice is mainly caused by the inflammatory reaction resulting from the lack of Treg cells.